1972
DOI: 10.1002/pssb.2220490132
|View full text |Cite
|
Sign up to set email alerts
|

Structure factor and atomic distribution in liquid metals by X‐ray diffraction

Abstract: X-ray diffraction patterns have been obtained from liquid metals (Al, Ga, In, TI, Pb, Sn, Bi) near the melting point. After calculating the structure factor (Fourier analysis), the atomic radial distribution function was evaluated from which interatomic distance and coordination number were obtained. It has been shown that the ratio (K,/K,) of the position of the first peak ( K , ) to that of the second peak (K,) in the structure factor is a very useful parameter to represent the structure of liquid metals.Ron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The ratio ($2/(^1) of the positions of the second and first maximum is almost constant (^1.85) (see Table 1) and nearly equal to the value (^ 1.83) found for molten alkali metals. The structure factors of molten alkaline earth metals thus look similar to those of the most simple metals such as the alkali metals, in contrast to molten tin, bismuth, and others, which show a subsidiary maximum on the high angle side of the first peak 5 . It is well known that this general form of the structure factor at temperatures just above the melting point agrees with that of the hard sphere model 13 with packing density r\ -0.45, within the first approximation.…”
Section: Structure Factor and Atomic Radial Distribution Functionmentioning
confidence: 71%
See 2 more Smart Citations
“…The ratio ($2/(^1) of the positions of the second and first maximum is almost constant (^1.85) (see Table 1) and nearly equal to the value (^ 1.83) found for molten alkali metals. The structure factors of molten alkaline earth metals thus look similar to those of the most simple metals such as the alkali metals, in contrast to molten tin, bismuth, and others, which show a subsidiary maximum on the high angle side of the first peak 5 . It is well known that this general form of the structure factor at temperatures just above the melting point agrees with that of the hard sphere model 13 with packing density r\ -0.45, within the first approximation.…”
Section: Structure Factor and Atomic Radial Distribution Functionmentioning
confidence: 71%
“…The experimental arrangement and operating procedure for the X-ray measurements on high-temperature melts have been fully discussed in 5 . All data were obtained with a combination of Mo and Cu radiations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the resistivity for K, Al, Sn and Bi by using Ziman's formula comsidering both the experimental structure factor α(q) [24,25] and the theoretical value based on a hard sphere model as obtained here. The results with different screeming functions are tabulated in Table I and II (also the values of Ω0, kF, m* and σ are tabulated in Table III).…”
Section: Theorymentioning
confidence: 99%
“…3) [2][3][4], in contrast to a symmetrical profile of simple liquid metals. The origin of the shoulder in S (Q) of liquid Bi was theoretically studied and it was found that an effective pair potential with a ridge in the repulsive component could reproduce the shoulder [5,6].…”
Section: Introductionmentioning
confidence: 99%